A pilot study of workplace violence towards paramedics. Issue 11 (22nd October 2007) - Boyle, Malcolm; Koritsas, Stella; Coles, Jan; Stanley, Janet
Abstract : Background: International studies have shown that some 60% of paramedics have experienced physical violence in the workplace, and between 21–78% have experienced verbal abuse. To date, there is no Australian literature describing Australian paramedics' experience of workplace violence. Objective: To identify the percentage of paramedics who had experienced six different forms of workplace violence. Methods: A questionnaire was developed to explore paramedics' experience of workplace violence. Six forms of violence were included: verbal abuse, property damage or theft, intimidation, physical abuse, sexual harassment, and sexual assault. The questionnaire also included a series of demographic questions. The questionnaire was piloted using a reference group and changes made accordingly. The questionnaire was distributed to 500 rural Victorian paramedics and 430 metropolitan South Australian paramedics. Ethics approval was granted for this study. Results: The overall response rate was 28%, with 75% being male and 25% female. The median age of respondents was 40.7 years, range 21–62 years. The median number of years experience as a paramedic was 14.3 years, range 6 months to 39 years. There were 87.5% of paramedics exposed to workplace violence. Verbal abuse was the most prevalent form of workplace violence (82%), with intimidation (55%), physical abuse (38%), sexual harassment (17%), and sexual assault (4%). Conclusion: This study lays the foundation for further studies investigating paramedic experience of workplace violence. This study demonstrates that workplace violence is prevalent for paramedics and highlights the need for prevention and education within the profession.